MICROSTRUCTURAL FEATURES AND MECHANICAL PROPERTIES OF AISI430 FERRITIC STAINLESS STEEL WELDS - A REVIEW - Musa, Abdulrahman; Dauda, E. T.; Bello, K. A. (FUDMA JOURNAL OF SCIENCES, 2020)
The lower cost of ferritic stainless steels together with their excellent resistance to stress corrosion cracking contributed to their current growth requirements and consumption in many industries particularly, petrochemical, marine, power plant, automobile and other engineering applications, where the nickel free steels are being consumed. However, the application of ferritic steel is limited especially, in those areas that require welding for fabrication of components because of poor ductility and notch impact toughness of its weld section due to the grain growth. Different techniques have been explored by several researchers to control the grain features of the weld zone in order to minimize these problems. In the present study, a review of these different techniques in relation to the microstructure and mechanical properties such as notch impact toughness, tensile strength, ductility and hardness was specifically carried out to create a better understanding on the microstructural-properties relationship in ferritic stainless steel weldments. Previous studies have proven that AC-TIG welding mode is the most effective technique for welding ferritic stainless steels and reported mechanical properties improvement of about 65% of the base metal. Finally, it can be concluded from the findings that, the net energy input and the rate of heat transfer during ferritic stainless steel welding mainly determine the resulting microstructure of the welds and hence, the mechanical properties.
Keywords: Microstructure, grain growth, mechanical property, ferritic stainless steel weld, welding techniques